On the Generalized Ulam-Hyers-Rassias Stability of Quadratic Mappings in Modular Spaces without Δ2-Conditions. (18th May 2015) - Wongkum, Kittipong; Chaipunya, Parin; Kumam, Poom
Abstract : We approach the generalized Ulam-Hyers-Rassias (briefly, UHR) stability of quadratic functional equations via the extensive studies of fixed point theory. Our results are obtained in the framework of modular spaces whose modulars are lower semicontinuous (briefly, lsc) but do not satisfy any relatives ofΔ 2 -conditions.